Factors Influencing Long-Term Home Care Utilization by the Older Population: Implications for Targeting - Lee, Taewha; Kovner, Christine T.; Mezey, Mathy D.; Ko, Il-Sun (Public health Nursing, 2001)
This research was designed to explore factors that affect the choice of long‐term care modalities in the older population and to discuss the appropriate target population of home health care services within the entire long‐term care system. The study subjects' activities of daily living limitations, cognitive status, and sociodemograhic data at the time of admission were obtained from retrospective chart reviews. The sample included 134 older subjects who were receiving long‐term care from a Long‐Term Home Health Care Program or a nursing home in New York City. The results indicated that Long‐Term Home Health Care Program use by older persons was characterized by a higher rate of being admitted from private homes, less cognitive impairments, less limitations in activities of daily living, and younger age than older patients who were nursing home residents. Consequently, in the choice of different care modalities, health‐related factors of the older population were found to be more important predictors than sociodemographic characteristics or support system. The implication to both nurses and researchers is the development of eligibility criteria that captures the unique characteristics of disabled older persons in each of the different long‐term care programs to serve them better in a cost‐effective manner.